Tingkat Motivasi Masyarakat Terhadap Olahraga Sepeda Selama Pandemi Covid 19 di Pekanbaru - Febridho zam (Jurnal Inovasi Olahraga, 2026)
The background of this problem is the increasing trend of cycling sports in the city of Pekanbaru during the current covid 19 pandemic. The purpose of this study was to determine the level of community motivation for cycling during the COVID-19 pandemic in Pekanbaru. This type of research is descriptive quantitative research. The population in this study is the community of bicycle hobbyists in the city of Pekanbaru totaling 300 people. The sampling technique uses a accidental sampling, count of samples in this study were 30 people. The instrument of this research is a questionnaire. The conclusions that can be drawn from this study are: the level of motivation for cycling during the covid19 pandemic in the city of Pekanbaru is categorized as high. The average respondent's answer was 61.0%. This percentage is quite high because it lies between 51% - 75%.